Teacher research in teacher education: Emancipatory potential in discouraging times - Schwarz, Gretchen; Ray, Brandi (Journal of Interdisciplinary Studies in Education, 2018)
In a time in which teachers and teacher educators live under constant disparagement, authentic teacher research has the potential to give teachers a voice in ongoing professional development as well as school improvement. Two teacher educators share their experience implementing teacher research among pre-service teachers, acknowledging pitfalls and successes. The current “state” of teacher research is described and benefits of teacher research summarized. Despite obstacles, teacher research can be transformational for teachers and their students, even emancipatory as teachers listen to their students and seek better ways of doing school.